(untitled) (Communication & Society, 2018)
More than two decades after printed newspapers began to be threatened by digital formats, it seems appropriate to study the current situation both in terms of the production and updating of content and the way in which they attract and retain readers who predominantly prefer social networks. This process not only affects the media since everything is becoming digital: books, appliances, shopping and, above all, lifestyle. And adapting to new environments is becoming more difficult than in other industrial revolutions. The objective of this paper is to analyse some of the causes that have brought newspapers to this situation that negatively affects not only editors but everyone working in the media, and that study suppose to the calculation of the number of most active updates, hours, week and the sections within the digital newspapers. In addition to the technological challenges, this article shall also assess the reading environment, the difficulty that newspapers have, digital formats included, in attracting the attention of readers, who have their own perception of the media.